Emission identification and health risk potential of allergy-causing fragrant substances in PM2.5 from incense burning - Kuo,S. (Elsevier BV, 2015)
© 2015 Elsevier Ltd. We investigated the emission characteristics of the allergenic aromatics eugenol and related compounds and vanillin from the incense powder and the PM2.5 emitted from burning Hsin Shan (HSIN), Shang Chen (SC), Shang Lao Shan (SLS) and Lao Shang Tou (LST) incense sticks. The powder produced 590.7-72.5μg of fragrant compounds g-1 of incense powder, ranking HSIN>>SLS>LST~SC, with vanillin representing 65.83-71.46% of the total, while the PM2.5 produced a higher 870.8-593.7μg of fragrant compounds g-1 of incense, ranking HSIN>>SC>>LST>SLS, with methyl isoeugenol the most prevalent compound, at 48.13-56.59% of the total, followed by vanillin. Burning caused some transformation of isoeugenol and methyl isoeugenol into the cis-type and hence both trans and cis types were present in the PM2.5. The ratio of total fragrant compounds in smoke PM2.5 to the content per gram of incense powder (IPt ratio) in the four types of incense ranged from 1.153 (SLS) to 1.507 (SC), indicating that incense powder produces a substantial amount of total fragrant compounds when burned. The ratio of fragrant emission factors in smoke PM2.5 to the content per gram of incense powder (IPs ratio) of methyl eugenol, vanillin, and eugenol was <1.0, indicating that burning destroyed these allergenic species. However, the IPs ratios of methyl isoeugenol and isoeugenol in the four types of incense reached as high as 5.171-8.924 and 2.735-4.301, respectively. The IPt and IPs ratios indicate an increased risk of allergenic reaction from the smoke from incense. Cluster analysis was conducted on the IPs ratios of incense and the total amounts of allergenic fragrant compound emissions were evaluated, which showed that HSIN incense possesses the highest allergenic potential and LST the lowest.